Metformin Impacts Human Syncytiotrophoblast Mitochondrial Function from Pregnancies Complicated by Obesity and Gestational Diabetes Mellitus in a Sexually Dimorphic Manner - Jessica F. Hebert; Leslie Myatt (MDPI AG, 2023)
Maternal obesity and gestational diabetes mellitus (GDM) are associated with placental dysfunction, small for gestational age (SGA) offspring, and programming of adult-onset disease. We examine how metformin, commonly used to treat type A2 GDM, affects placental metabolism as well as mitochondrial content and function. Syncytiotrophoblasts (STBs) were prepared from placentas of male and female fetuses collected at term cesarean section from lean (pre-pregnancy BMI < 25), obese (BMI > 30), and obese A2GDM women. Metformin treatment (0.001-10 mM) of STB caused no change in non-mitochondrial respiration but significant concentration-dependent (1 and 10 mM) decreases in basal, maximal, and ATP-linked respiration and spare capacity. Respiration linked to proton leak was significantly increased in STB of male A2GDM placentas at low metformin concentrations. Metformin concentrations ≥1 mM increased glycolysis in STB from placentas from lean women, but only improved glycolytic capacity in female STB. Whereas metformin had little effect on superoxide generation from male STB of any group, it gave a concentration-dependent decrease in superoxide generation from female STB of lean and obese women. Fewer mitochondria were observed in STB from obese women and male STB from lean women with increasing metformin concentration. Metformin affects STB mitochondrial function in a sexually dimorphic manner but at concentrations above those reported in maternal circulation (approximately 0.01 mM) in women treated with metformin for GDM.